Cardiology an illustrated textbook [CD] - Chatterjee, Kanu; Anderson, Mark; Heistad, Donald; Kerber, Richard E. (New Delhi : Jaypee Brothers Medical Publishers, 2012)
Contiene videos de alta calidad de la ecocardiografía.
Interactive DVD-Rom with ECHO Loops
Keywords: CARDIOLOGY -- AUDIOVISUAL; CARDIOGRAFIA -- AUDIOVISUAL